Examining the influence of athletes` punishment experiences on decisions to cease participation in competitive hockey - Battaglia, A.; Kerr, G.; Stirling, A. (International Journal of Sport and Exercise Psychology, 2020)
This study examined athletes` experiences of punishment in competitive hockey and the potential influence of these experiences on their decisions to cease participation in the sport. Semi-structured interviews were conducted with 10 former female and male competitive hockey athletes, 18-19 years of age. Data were analysed using inductive thematic analysis. Participant accounts revealed that yelling, benching, and physical conditioning exercises were forms of punishment experienced regularly throughout their hockey involvement. These punishment experiences reportedly had negative effects on the participants` perceived athletic worth, enjoyment and fun in hockey, and sport relationships, and enhanced their interests in other activities. Findings are interpreted to suggest that punishment experiences contributed to athletes` decisions to cease participation in competitive hockey. Recommendations for future research and practice are suggested.